TIME OF DIABETIC ULCER FOOT SUFFERING AND DEPRESSION SYMPTOMS IN ULIN GENERAL HOSPITAL BANJARMASIN - Rizka Dwi Puteri; Yulizar Darwis; Farida Heriyani (Berkala Kedokteran, 2017)
Abstract: Diabetic foot ulcers are one kind of chronic complication of diabetes mellitus in the form of an open wound on the skin’s surface and may be accompanied by local tissue death.  Long term suffering of diabetic foot ulcers with physical and psychological changes may cause symptoms of depression. The aim of this study was to determine the correlation between long term suffering of diabetic foot ulcers and symptoms of depression in RSUD Ulin Banjarmasin. This was an analytic observational study with a cross sectional method. The samples were taken from systematic random sampling which resulted in 50 samples. Data was collected by interviewing samples with basic data questions to determine long term suffering of diabetic foot ulcers and Beck Depression Inventory-II (BDI-II) questionnaire to determine symptoms of depression. The data was analyzed by using chi square with 95% significance level. The results were 36 samples suffered for ≤8 weeks and 14 samples suffered for >8 weeks, meanwhile 31 samples with symptoms of depression and 19 samples without symptoms of depression. The result of statistic test found p value =0,002. In conclusion, there is a correlation between long term suffering diabetic foot ulcers and symptoms of depression in RSUD Ulin Banjarmasin.   Keywords: long term suffering, diabetic foot ulcers, symptoms of depression, Beck Depression Inventory-II (BDI-II), RSUD Ulin Banjarmasin